Physicochemical and microbiological aspects of goat milk - Cruz, Andrea Viana da; Oliveira, Ana Lídia Brito de; Silva, Bruno Daniel Sales da; Silva, Elton Alex Correa da; Lima, Allana Lais Alves (Scientia Agraria Paranaensis, 2021)
Goat milk is a high-quality food of fundamental importance for thousands of people involved in the socioeconomic development of this product, and dairy goat farms are well estasblished in the agricultural scenario, especially when analyzing small rural producers. The quality of goat milk is defined by its physicochemical and microbiological parameters. Adequate hygiene, handling, and management practices, from obtaining milk to commercialization, are of fundamental importance for guaranteeing food quality and safety for the consumer market. It is important to know the microbiological quality of milk, since it belongs to one of the most relevant food groups for the population. Brazilian legislation establishes minimum quality requirements for goat milk intended for human consumption in Normative Instruction 37 ̸2000. The goals of this literature review were to present the issues related to the physicochemical composition, microbiological aspects, and nutritional properties of goat’s milk as a reference measure and to highlight some characteristics. Despite the similarities with the milk of other animal species, goat milk is a unique product, and the study of this raw material is of great importance for industry as well as for the scientific community.